Innovatıon In Scıence, Educatıon, And Productıon Integratıon As A Successor - U AdizovaSevaraYusupovna (International Journal of Advanced Science and Technology, 2020)
The article covers the philosophical essence of the cooperation between higher education, science and innovation in production, based on the analytical conclusions of the practical work carried out to improve scientific research activities in the system of higher educational institutions, the unity of the components of the national model in the national program of Personnel Training. At the same time, the article provides an overview of the origin of innovation from the succession in the holiness of each object, the improvement in the processes of Nature, Society and human thinking, including Science, Education, production, their complementarity, the legislation of the principle of "knowledge through knowledge" and the approach to the system of "teacher".